The ratio of intratumoral CD15+ neutrophils to CD8+ lymphocytes predicts recurrence in patients with gastric cancer after curative resection - Junichiro Watanabe; Takashi Kimura; Zenichiro Saze; Naoya Sato; Yasuhide Kofunato; Teruhide Ishigame; Ryo Okada; Akira Kenjo; Koji Kono; Shigeru Marubashi (Cancer Reports, 2024)
Abstract Background An elevated neutrophil‐to‐lymphocyte ratio (NLR) in peripheral blood is an independent prognostic indicator of various cancers. Aims In this study, we aimed to investigate the prognostic relevance of the intratumoral immune cell balance in gastric cancer. Methods and Results The study included 82 patients who underwent curative resection for gastric cancer. The intratumoral cluster of differentiation (CD) 15‐ and CD8‐positive cells were evaluated using immunohistochemical staining. Additionally, clinicopathological factors and prognoses were analyzed. Patients with high intratumoral CD15/CD8 ratios had significantly lower overall survival (OS) and relapse‐free survival (RFS) compared to those with low CD15/CD8 ratios (p = .0026 and p < .0001, respectively). Additionally, a high CD15/CD8 ratio was associated with lymph node metastasis (p = .019). Patients with high NLR had a significantly lower RFS than those with low NLR (p = .0050). Multivariate analysis revealed that the intratumoral CD15/CD8 ratio, NLR, and venous invasion were independent prognostic indicators of RFS (CD15/CD8 ratio: p < .001, hazard ratio (HR) = 14.7, 95% confidence interval (CI) = 3.8–56.8; NLR: p = .010, HR = 5.4, 95% CI = 1.5–19.6; venous invasion: p = .005, HR = 7.4, 95% CI = 1.8–29.7). Conclusion In summary, we found that the intratumoral CD15/CD8 ratio is an independent prognostic factor following gastric cancer resection and its increase is associated with lymph node metastasis and microscopic lymph vessel invasion. Immunological evaluation with additional aspects of innate immunity may be useful in predicting cancer prognosis.